A trend in publishing artificial intelligence personalized education: Enhancing learning experiences for university students - Dean Nelson Mojolou; Faerozh Madli; Helmina Thomas; Stephen Laison Sondoh Jr.; Erick Karunia (Global Academic Excellence, 2024)
This bibliometric analysis explores the emerging landscape of Artificial Intelligence (AI) in personalized education, revealing a significant growth in research publications from 2004 to 2024. The study examines research trends, publication patterns, and collaborative efforts across disciplines, with findings indicating a sharp increase in publications from 200 per year in 2020 to a projected 500 by 2024. Analyzing data from Scopus, the research highlights AI's transformative potential in higher education, with Social Sciences (46%) and Computer Science (23.3%) dominating the publication landscape. Key themes include personalized learning, adaptive learning technologies, and integrating advanced tools like ChatGPT while addressing critical ethical considerations around data privacy and responsible AI implementation. The global research ecosystem, led by the United States, United Kingdom, and China, demonstrates a collaborative approach to developing AI-driven educational solutions that promise to enhance individual learning experiences and outcomes for university students.